2016
DOI: 10.1093/infdis/jiv485
|View full text |Cite
|
Sign up to set email alerts
|

World Health Organization's Innovative Direct Disbursement Mechanism for Payment of Grassroots Immunization Personnel and Operations in Nigeria: 2004–2015

Abstract: Background. Following the 1988 World Health Assembly resolution to eradicate polio, the government of Nigeria, with support from partners, has been implementing several rounds of supplementary immunization activities (SIAs) each year. In addition to the technical requirements, the success of the polio eradication initiative depends on timely provision of adequate financial resources. Disbursement of funds for SIAs and payment of allowances to numerous vaccination personnel at the grassroots level are enormous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…Availability of a partner bank in-country with capacity to support mobile phone-based funding disbursement important to intervention delivery. [ 53 ] Private sector engagement Transformative Statistically significant increase in coverage for selected antigens in intervention area by comparison with controls. Community-embeddedness of the intervention – through engagement of local councils – was important in supporting demand for vaccination through the public-private partnership.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Availability of a partner bank in-country with capacity to support mobile phone-based funding disbursement important to intervention delivery. [ 53 ] Private sector engagement Transformative Statistically significant increase in coverage for selected antigens in intervention area by comparison with controls. Community-embeddedness of the intervention – through engagement of local councils – was important in supporting demand for vaccination through the public-private partnership.…”
Section: Resultsmentioning
confidence: 99%
“…The study on disbursement mechanisms did not consider any of our primary outcomes, but did address intermediate effects (secondary review outcomes) including successful completion of health worker payments, widely understood to be a key operational challenge for programme delivery in LMICs in general, and humanitarian settings in particular [ 53 ]. In this intervention, the WHO oversaw direct disbursement to the local level through a variety of activities including a newly introduced e-payment system, the establishment of close-to-facility payment sites and later the use of mobile payment systems, with reconciliation of funding distribution through partner meetings and other forms of information exchange.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These included two that looked at macro-level financing -specifically the value or otherwise of development aid in promoting improved health outcomes, including for vaccination, and system-strengthening in Gavi supported countries (47,48); one study that considered private sector provider engagement in routine immunisation provision (49); and four that considered in one way or another improvements to local level incentives for vaccination delivery (50)(51)(52)(53). Of these four, three studies considered explicit incentivisation to facilities or health workers via pay for performance (P4P) (50)(51)(52); and one considered improvements to disbursement of programme funds to local level to promote vaccination delivery as a means of reducing the risk of delayed payment to HCWs (53). Most of these studies were from low-income settings in Sub-Saharan Africa, and 5 of the 6 considered interventions in conflict or post-conflict environments.…”
Section: Health Financingmentioning
confidence: 99%
“…In a study conducted prior to 2004, researchers found that the success of Nigeria’s polio eradication initiative depended on timely, direct, and full payment of vaccination personnel [ 7 ]. Following the establishment of a Mobile Money payment system for frontline workers, challenges with making timely, direct, and full payments to workers were overcome.…”
Section: Introductionmentioning
confidence: 99%